A COMPREHENSIVE REVIEW OF NOVEL MODULATOR THE GABAA RECEPTOR, BREXANOLONE FOR THE TREATMENT OF POST-PARTUM DEPRESSION - SHUKLA, AJAY KUMAR; MISRA, SAURAV (International Journal of Current Pharmaceutical Research, 2025)
Postpartum Depression (PPD), a significant depressive disorder that starts during pregnancy and also can occur postpartum. Similar to other types of depression, it is characterised by sadness and/or loss of interest in previously enjoyed activities as well as a decreased capacity for pleasure. It can also be accompanied by symptoms like cognitive impairment, feelings of guilt or worthlessness, or suicidal thoughts. PPD has a detrimental effects on the mother itself as well as child and whole family. Up to 20% of women may experience postpartum depression after giving birth. It has been linked to decreased mother-infant bonding and negative impacts on the child's cognitive, behavioural, and emotional growth. There were no approved drugs to treat postpartum depression up until recently. Psychotherapy and drugs were used as treatments, although not all women experience a positive response or remission, and sometimes the response is delayed. A naturally occurring neuroactive steroid called allopregnanolone, its serum levels sharply decrease after giving birth. It has been hypothesised that this hormone fluctuation contributes to the pathophysiology of postpartum depression. It is given as a 60-hour continuous infusion while being monitored and is expected to affect neuronal excitability by acting as an allosteric modulator of γ-aminobutyric acid-A receptors. In this review, we have summarized brexanolone, first dug approved by US Food and Drug Administration (US FDA) for the treatment of postpartum depression. Evidences from in silico, in vitro, in vivo and clinical studies have demonstrated that it provides rapid and effective alleviation from depressive symptoms.